Pengaruh Penerapan Clinical Pathway pada Peresepan Antibiotik Pasien Tifoid Anak di Rumah Sakit Swasta X Kota Bogor: Effect of Clinical Pathway on Antibiotic Prescribing for Children Typhoid Patients at Hospital X Bogor - Oriza Safrini; Dian Ratih Laksmitawati; Hesty Utami Ramadaniati (Jurnal Sains dan Kesehatan, 2023)
Typhus occurs almost all over the world. To reduce the variation of antibiotics in hospitals, especially for inpatients, a Clinical Pathway was created. This study aims to determine the effect of the application of a clinical pathway on antibiotic prescribing in pediatric typhus patients in the inpatient room of X Private Hospital, Bogor. This research is a comparative observational study that compares the prescribing of antibiotics before the implementation of the clinical pathway and after the application of the clinical pathway. The Chi-square test was used to compare the rationality of antibiotic use, length of stay, and solubility of antibiotic choices with guidelines. A sample of 81 people was obtained before the application of the clinical pathway and 78 people after the application of the clinical pathway. Before the implementation of the clinical pathway, the rational use of antibiotics was 48.88% and after the application of the clinical pathway, it increased to 67.05%. (p = 0.016). Based on the results of statistical tests, there were 52 patients (64.19%) who had a length of stay ? 5 days before the implementation of the clinical pathway and 68 patients (87.17%) before the implementation of the clinical pathway (p=0.001). As much as 68.89% of the selection of antibiotics before the application of clinical pathways according to management guidelines and after the application of clinical pathways increased to 88.64%. (p = 0.001). The conclusion from this study is that the application of a clinical pathway at Hospital X Bogor City has increased the rationality of using antibiotics Keywords: Antibiotic, Clinical pathways, Gyssen, Typhoid Abstrak Tifoid terjadi hampir di seluruh dunia. Untuk mengurangi variasi antibiotik di rumah sakit khususnya pada pasien rawat inapmaka dibuatlah Clinical pathway. Adapun tyjuan penelitian ini adalah untuk mengetahui pengaruh implementasi clinical pathway terhadap peresepan antibiotik untuk pasien Tifoid anak di ruang rawat inap Rumah Sakit Swasta X di Bogor. Penelitian ini bersifat observasional comparative study membandingkan peresepan antibiotik sebelum penerapan clinical pathway dan setelah penerapan clinical pathway. Uji Chi square digunakan untuk membandingkan rasionalitas penggunaan antibiotik, lama rawat dan kesesuaian pilihan antibiotik dengan pedoman. Diperoleh sampel sebanyak 81 orang sebelum penerapan clinical pathway dan 78 orang setelah penerapan clinical pathway. Sebelum penerapan clinical pathway penggunaan antibiotik rasional sebanyak 48.88% dan setelah penerapan clinical pathway meningkat menjadi 67.05%. (p = 0,016). Berdasarkan hasil uji statistik menujukkan pasien yang memiliki lama rawat ? 5 hari sebelum penerapan clinical pathway sebanyak 52 pasien (64.19%) dan sebelum penerapan clinical pathway sebanyak 68 pasien (87.17%) (p = 0,001). Sebanyak 68,89% pemilihan antibiotik sebelum penerapan clinical pathway telah sesuai dengan pedoman tata laksana dan setelah penerapan clinical pathway meningkat menjadi 88.64%. (p = 0,001). Adapun kesimpulan dari penelitian ini adalah implementasi clinical pathway di Rumah Sakit X di kota Bogor telah meningkatkan rasionalitas penggunaan antibiotik. Kata Kunci: Antibiotik, Clinical pathway, Gyssen, Tifoid